Development of Concrete Flat Sheetpile Joint Model As A Soil Retaining Wall - Billy Muchtar; Agustinus Purna Irawan; Masdar Helmi (Interdisciplinary Social Studies, 2025)
The problem of soil retaining wall stability is an important concern in civil construction, especially in the use of concrete sheetpile as an efficient and durable structural solution. However, the design of concrete Sheetpile joints still faces challenges in ensuring structural strength, waterproofness, ease of installation, and resistance to extreme environments. This study aims to develop an optimal concrete flat Sheetpile connection model as a soil retaining wall. The research method involves experimental analysis and numerical simulation on various configurations of Sheetpile joints, including testing of mechanical strength, waterproofness, and material testing against environmental factors. The collected data will be analyzed using an experimental design approach and model validation with structural software. Predicted results show that the developed connection model will improve the stability of the ground retaining wall with better installation time efficiency, while meeting safety and sustainability standards. The continuation of the research is directed at the application of the connection model in actual construction projects to evaluate performance in the field and refine the model based on practical implementation feedback.